The European Union in international organisations and global governance : recent developments - Kaddous, Christine (Modern studies in European law., 2015)
The European Union is a key participant in international organisations with its involvement taking different forms, ranging from full membership to mere observer. Moreover, there is also not only one status of observer, but different ones depending on the constituent charters of the organisations. This book provides a comprehensive overview of the participation of the EU in five international organisations: the UN, the ILO, the WTO, the WHO and the WIPO. It identifies its role and influence in diverse areas of global governance, such as foreign policy, peace, human rights, social rights, trade.